Effects of Low Dose Neutron-Gamma Field on Cell Cycle and Damage of Human Lymphocytes - Jinghong Fu; Guangfen Du; Haiqing Wang; Chenxing Liao; Yuyan Zhang; Weiguo Li (Dose-Response)
Purpose: The aim is to investigate the response of peripheral blood lymphocytes to a low-dose neutron-gamma field. Methods: The human peripheral blood was exposed to low-dose neutron-gamma radiation ex vivo. Flow cytometry was utilized to evaluate the changes in cell cycle and protein levels of p21, CDK2, and γH2AX. qPCR analysis was conducted to investigate the mRNA transcription of p21 and CDK2. The chromosomes aberration and micronucleus rate in peripheral blood lymphocytes were observed by microscope. Results: Within the radiation dose range of 0-5976 μGy, compared to the “0” dose group, there was an increase in the proportion of cells in G1 phase and a decrease in the proportion of cells in G2 phase. Additionally, there was an upregulation of p21 and γH2AX protein expression, a downregulation of CDK2 protein expression, and an increase in transcription levels of p21 and CDK2 mRNA. Furthermore, there was an elevation in the rate of chromosome aberrations in peripheral blood lymphocytes; however, no significant change of micronuclei rate was observed. Conclusions: The response of human lymphocytes to low dose neutron gamma irradiation can be reflected by the changes of cell cycle, chromosome aberration and RPS18 expression.